2020
DOI: 10.1186/s12885-020-07543-4
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-wide DNA methylation and risk of breast cancer: a systematic review

Abstract: Background DNA methylation is a potential biomarker for early detection of breast cancer. However, robust evidence of a prospective relationship between DNA methylation patterns and breast cancer risk is still lacking. The objective of this study is to provide a systematic analysis of the findings of epigenome-wide DNA methylation studies on breast cancer risk, in light of their methodological strengths and weaknesses. Methods We sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Genes [e.g., the DNA repair gene, O-6-methylguanine-DNA methyltransferase (MGMT)] within these regions were largely silenced in BC cells and the loss of DNA methylation in these regions was accompanied by the formation of repressive chromatin, indicating a widespread DNA hypomethylation for gene regulation through chromatin alteration (62). A recent systematic analysis found an association between global blood-derived DNA hypomethylation with a higher risk of developing BC, and the strength of the association tends to be weak for long period follow-up, indicating that global DNA methylation may be a short-term predictor of the risk of developing BC (64).…”
Section: Epigenetic Alterations In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Genes [e.g., the DNA repair gene, O-6-methylguanine-DNA methyltransferase (MGMT)] within these regions were largely silenced in BC cells and the loss of DNA methylation in these regions was accompanied by the formation of repressive chromatin, indicating a widespread DNA hypomethylation for gene regulation through chromatin alteration (62). A recent systematic analysis found an association between global blood-derived DNA hypomethylation with a higher risk of developing BC, and the strength of the association tends to be weak for long period follow-up, indicating that global DNA methylation may be a short-term predictor of the risk of developing BC (64).…”
Section: Epigenetic Alterations In Breast Cancermentioning
confidence: 99%
“…As described above, substantial evidence has supported the associations between obesity and DNA methylation (80)(81)(82)91,92); however, the cause and effect remains to be defined. It is also well known that alterations in DNA methylation patterns are common epigenetic aberrations in BC (64,93). Dysregulated DNA methylation is directly associated with BC pathogenesis by controlling significant processes, including gene transcription, post-translation, the remodeling of chromatin, the imprinting of a genome, etc.…”
Section: Obesity Dna Methylation and Breast Cancermentioning
confidence: 99%
“…However, there are some limitations to considering global methylation as a stable and strong biomarker for breast cancer risk determination. As pointed out by Ennour-Idrissi et al, the methylation signatures are subject to reversibility and variability based on tissue type [ 47 ]. To increase the precision of global methylation as a biomarker for breast cancer risk detection, collective methylation change in the global CpG landscape is being considered [ 48 ].…”
Section: Scope Of Primary Prevention In Breast Cancer From a Detailed Epigenetic Perspectivementioning
confidence: 99%
“…A developing avenue of research involves examining DNA methylation in surrogate tissues, such as blood. A number of studies have shown that epigenome-wide DNA methylation in white blood cells, especially at non-promoter regions, is associated with decreased breast cancer risk (reviewed in [ 23 ]).…”
Section: Introductionmentioning
confidence: 99%